Photo-degradation of renewable biopolymer blended with thermoplastic high density polyethylene (HDPE) - Sulong, Nurulsaidatulsyida (2022)
High Density Polyethylene (HDPE) is one type of thermoplastic with varies applications but non-biodegradable material while biopolymer (BP) is environmentally friendly and degradable materials. However, BP has poor mechanical characteristics and restrict their capacity for varying in applications. Therefore, in this study, HDPE was blended with BP in liquid and particle form to produce BPL/ BPP. The composition ratio of BP blended with HDPE were 5, 10, 15, 20, 25 and 30% wt/wt of BP. These BP, HDPE, BPL/ BPP with different percentages of loading then were exposed to different UV exposure (250h, 500h, 750h, 1000h, 2000h, and 3000h) to identify the photo-degradation process. The formation of functional group of urethane linkages and other absorption peak was identified by using Fourier Transform Infrared Spectroscopy (FTIR). Norrish I and Norrish II reaction was taking place that produced ketone, amide group and carboxylic acid when increase in UV irradiation exposure that identified the photo-degradation process occurs in BPL/ BPP. By increasing percentages of BP loading, Melt Flow Index (MFI) shows decreasing in results indicate good flowability and improved its processability. Dynamic Mechanical Analysis (DMA) also shows a single peak of Tg indicated miscibility blending of BPL and BPP in all percentages of loading. BPL and BPP show higher tensile stress and hardness results as compared to BP. This is revealed the new blended polymer enhanced the mechanical properties of BP itself. Meanwhile, Scanning Electron Microscope (SEM) of BP shows brittle fracture morphology while HDPE shows ductile fracture and BPL or BPP show ductile to brittle morphological structure due to increasing in percentages of BP loading. Ultimately, BPL30-3000h, spider-web-like structure appeared while for BPP30-3000h, revealed a fine lamellar type of structure. Hence, BPL/ BPP successfully produced, and photo-degradation process occur and having good mechanical properties as compared to single materials itself (BP or HDPE).